A good or bad transition from school to work: who is responsible?. Issue 8 (2nd November 2015) - Defloor, Bart; Van Ootegem, Luc; Verhofstadt, Elsy
Abstract : Purpose: – The purpose of this paper is to analyse the determinants of the quality of the first job in Flanders (Belgium). The authors differentiate between circumstances on the one hand – individual characteristics beyond the control of the individuals such as gender or the unemployment rate at labour market entry – and efforts on the other hand – characteristics that are at least partly under the individuals' control such as their educational attainment or labour motivation. The authors specifically take into account the fact that the former might influence the latter. A better understanding of the effects of these determinants can help to formulate (labour market) policy proposals (to ameliorate the school-to-work transition) that are responsibility-sensitive. The authors use the distance function to construct a one-dimensional measure of job quality – based on a list of job characteristics – and explain the variation in job quality in terms of circumstances and efforts. The empirical analysis is based on the 1978 birth cohort of the Flemish SONAR data. The results show that the quality of the first job is to a large extent depending on personal efforts and that circumstances have a considerable influence on the efforts. For this reason circumstances influence job quality twice. This is especially the case for gender and for the educational attainment of the individual's mother. The labour market situation at labour market entry also plays a considerable role. Design/methodology/approach: – The authors use the distance function to construct a one-dimensional measure of job quality – based on a list of job characteristics – and explain the variation in job quality in terms of circumstances and efforts. The empirical analysis is based on the 1978 birth cohort of the Flemish SONAR data. Findings: – The results show that circumstances have a considerable influence on the efforts and for this reason circumstances influence job quality twice. This is especially the case for gender and for the educational attainment of the individual's mother. The labour market situation at labour market entry also plays a considerable role. Originality/value: – The paper contributes to the literature in several ways. First, it analyses the quality of the first job individuals get after leaving school and uses an equality of opportunity framework. This approach differs from an approach based on search duration or job satisfaction. Second, job quality is evaluated in a multidimensional way using the distance function. Third, the relation between job quality and circumstances – issues for which the individual is not responsible – and efforts – issues for which the individual is at least partly responsible – is investigated. The authors specifically take into account the fact that circumstances might influence efforts and investigate the consequences for labour market policy.